(30 الكلمات الجاوية ذات أصل قرآني في كتاب الإبريز لمعرفة القرآن العزيز (الجزء 9 إلى - TABIB ROHANI; ABD. AR-ROHIM (Rayah Al-Islam, 2016)
This study aims to reveal the words of java uptake derived from al-qur’an in the book of al-ibriz translation of the javanese language from juz 9 to 30, based on the existence of a very close relationship between the javanese language with al-qur’an since the entry islam in the land of java, because islam brings a culture that is not found in the foreign languages (Arabic) to communicate, for religious, politica, economic, and social needs. This study also intends to find out the changes in the meaning of words that occur in the words of java absorption derived from al-qur’an, also triying to apply it in teaching arabic for the people of java. In this study, the researcher uses an analytical description method that describes the subject of a proper study by comparing the two languages of the qur’an (Arabic) and javanese language by referring to arabic dictionary and the javanese language dictionary, then describing and analysing the words, researcher also tying to apply these words in the teaching of arabic for the people of java either in the from of ta’lim aswat, nash qiro’ah,hiwar, and istihqoq word. This study shows that in the book of al-ibriz translation of al-qur’an javanese language there are fifty words absorption of al-qur’an, this research also shows the existence of changes of meaning of the said uptake when switching into javanese language and divided into four categories, this research also shows that these absorption words can be applied in teaching arabic to the javanese in various ways and methods.